Model Perancangan Sistem Informasi Akuntansi Siklus Pengeluaran Kas Dengan Metode Rea Pada Lembaga Pengkajian Dan Pengembangan Sumber Daya Pembangunan LPPSP Di Kota Semarang - Sri Suyati (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2011)
Abstract Accounting Information Systems is a group of subsystems that process financial and non financial transactions that directly affect the processing of financial transactions. Subsystem consists of processing System Transaction Reporting System General Ledger / Financial and Management Reporting systems. REA is a conceptual modeling tool specifically designed to complement the structure in the design database. This type of entity in the REA model is divided into three categories, namely Resource, Events and Agents. REA diagram is used as supplementary documentation, which is useful for documenting the formation of advanced AIS. After the REA diagram is completed, REA diagram can be used to design a good relational database structure. To implement the REA diagram into a relational database required three steps: making a table for each entity and relationship N:M, define attributes for each table, and implement Relationship 1:1 and 1:N Key words: accounting information systems, internal control